Knowledge, attitudes, and education of senior dental students in tehran universities of medical sciences towards tobacco cessation counseling - Mohammadreza Khami; Shima Ghorbani; Mahdi Hasanpour (Tehran University of Medical Sciences, 2019)
Background and Aims: Due to high mortality rate and cost of smoking, WHO has emphasized on the role of dentists in smoking cessation among patients. The aim of the present study was to investigate the dental students, knowledge toward health consequences of smoking, their attitude towards smoking cessation activities, and their education programs in this field. Materials and Methods: In this cross-sectional study, the target group was senior dental students at Tehran and Shahid Beheshti Universities of Medical Sciences, and Azad and Shahed Universities. A questionnaire was used to collect data in addition to background information, on the knowledge, attitudes, and education towards tobacco cessation counseling in dental practice was administered to the students. The sampling method was census. Data were analyzed using oneway Anova followed by Turkey HSD post-hoc test for pairwise comparison. Results: Overall 138 students participated in this program (The response rate was 100%). Of the maximum achievable knowledge score (28), the average knowledge score in Tehran University was 22.8, in Shahid Beheshti University 20.31, in Azad University 22.31, and in Shahed University 22.16 (P=0.027) with significant statistical differences. However, But the average of attitude and education score of the students did not vary significantly (P>0.05). Conclusion: Most of the students had sufficient knowledge about the risks of tobacco use and positive attitude toward tobacco cessation counseling. It was concluded that the students would only pay attention to the principals of smoking cessation counselling when they actually believe in them. Therefore, in order to improve the performance of students, training should be given on tobacco cessation techniques at the dental schools, thus, that students could play an effective role in tobacco cessation counseling for patients.